2006 Fortieth Asilomar Conference on Signals, Systems and Computers 2006
DOI: 10.1109/acssc.2006.355005
|View full text |Cite
|
Sign up to set email alerts
|

A General Hardware/Software Co-design Methodology for Embedded Signal Processing and Multimedia Workloads

Abstract: Abstract-This paper presents a hardware/software co-design methodology for partitioning real-time embedded multimedia applications between software programmable DSPs and hardware based FPGA coprocessors. By following a strict set of guidelines, the input application is partitioned between software executing on a programmable DSP and hardware based FPGA implementation to alleviate computational bottlenecks in modern VLIW style DSP architectures used in embedded systems. This methodology is applied to channel es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…As an example, using the workload partition criteria for partitioning functionality between a programmable DSP core and system containing multiple hardware for a 3.5G HSDPA system, it has been shown that impressive performance results can be obtained. In studying the bottlenecks of such systems when implemented on a programmable DSP core in software, it has been found the key bottlenecks in the system to be the channel estimation, fast fourier transform (FFT), inverse fast fourier transform (IFFT), FIR filter, and to a lesser extent despreading and descrambling as illustrated in Figure 4 [9]. By migrating the 3.5G implementation from a solely software based implementation executing on a TMS320C64x based programmable DSP core to a heterogeneous system containing not only programmable DSP cores but also distinct hardware acceleration for the various bottlenecks, the authors achieve almost an 11.2x speedup in the system [9].…”
Section: Mimo Channel Equalization Acceleratormentioning
confidence: 99%
“…As an example, using the workload partition criteria for partitioning functionality between a programmable DSP core and system containing multiple hardware for a 3.5G HSDPA system, it has been shown that impressive performance results can be obtained. In studying the bottlenecks of such systems when implemented on a programmable DSP core in software, it has been found the key bottlenecks in the system to be the channel estimation, fast fourier transform (FFT), inverse fast fourier transform (IFFT), FIR filter, and to a lesser extent despreading and descrambling as illustrated in Figure 4 [9]. By migrating the 3.5G implementation from a solely software based implementation executing on a TMS320C64x based programmable DSP core to a heterogeneous system containing not only programmable DSP cores but also distinct hardware acceleration for the various bottlenecks, the authors achieve almost an 11.2x speedup in the system [9].…”
Section: Mimo Channel Equalization Acceleratormentioning
confidence: 99%
“…Several studies have addressed the task portioning of signal processing functions for wireless receivers [20,21]. However, these studies focus on projecting a single communication mode into the heterogeneous processing architecture.…”
Section: Software Defined Radio Architecturementioning
confidence: 99%
“…The task of system-level design is to trade-off an inexpensive and flexible software solution versus a high-speed hardware implementation. There are three main system level design approaches: hardware/ software co-design [9], platform-based design [10] and Model-driven Design [11]. Here the hardware refers to dedicated hardware component (ASIC) and Software refers to software executing on processor or ASIP.…”
Section: Introductionmentioning
confidence: 99%